FRI0161 Humoral and cell-mediated immune response to cow's milk proteins in behÇet's disease. (1st June 2001) - Triolo, G; Accardo-Palumbo, A; Ciccia, F; Ferrante, A; Mantione, C; Giardina, E; Licata, G
Abstract : Background: Behçet's disease (BD) is a multisystemic inflammatory disease characterised by a number of immunological variables. The relevance of these findings is not sufficient to support an autoimmune pathogenesis. Consumption of cow's milk proteins might be a risk factor for the development of autoimmune disease. Objectives: To investigate the humoral and cell-mediated immune response against cow's milk proteins in BD. Methods: Sera from 47 patients with BD and 38 healthy subjects were studied. Anti beta-casein (bC) and anti beta-lactoglobulin (bLG) antibodies were detected by ELISA. Peripheral blood mononuclear cells from 16 BD patients and from 8 healthy controls were cultured in the presence of PHA, beta-casein or beta-lactoglobulin and IL-4 and Interferon-gamma measured in the culture supernatants by ELISA. Results: Significant higher levels of anti-bC and anti-bLG were found in the sera of patients with active disease (anti-bC-IgA:1.89 ± 2.2 SDU;-IgG:3.64 ± 5.93; anti-bLG-IgA:2.07 ± 2.51;-IgG:1.72 ± 2.7) compared with those of inactive patients (anti-bC-IgA:0.68 ± 0.92;-IgG:0.83 ± 1.26; anti-bLG-IgA:0.70 ± 1.12;-IgG:0.37 ± 0.65) or controls. Higher levels of IFN-gamma but not IL-4 were found in the supernatants of active patient cultures but not in those of patients with inactive disease or controls in both bC and bLG studies. Levels were comparable to those obtained with PHA. Conclusion: The occurrence of anti-bC and anti-bLG in BD and studies on the cellular immune response with Th1 cytokine secretion might further support the putative role of cow's milk protein immune response in the pathogenesis of autoimmune disease and in particular of BD.